2017
DOI: 10.18632/oncotarget.18207
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting of IGF1R/mTOR pathway by miR-497 and miR-99a impairs hepatocellular carcinoma development

Abstract: Persistent activation of IGF1R/mTOR signaling pathway plays crucial role in the development of hepatocellular carcinoma (HCC). Therefore, our goal was to elucidate microRNAs (miRNAs) targeting IGF1R/mTOR and the therapeutic potential of single or dual miRNA on HCC development. In this study, we found that miR-497 and miR-99a that target the 3′-UTR of both IGF1R and mTOR were down-regulated in HCC human tissues and cell lines. Functional assay revealed that ectopic expression of miR-497 or miR-99a in HCC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…miR-187, miR-497, miR-99a, miR-592: IGF-1R activation, through the PI3K/Akt/mTOR axis, is responsible for cell proliferation, migration and invasion in HCC[ 27 ]. IGF-1R is a target of miR-187, miR-497, miR-99a and miR-592[ 28 - 30 ]. miR-187 was found downregulated in HCC tissues and cell lines: as reported by Han et al[ 29 ], the restoration of miR-187 leads to a significant arrest of HCC growth.…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-187, miR-497, miR-99a, miR-592: IGF-1R activation, through the PI3K/Akt/mTOR axis, is responsible for cell proliferation, migration and invasion in HCC[ 27 ]. IGF-1R is a target of miR-187, miR-497, miR-99a and miR-592[ 28 - 30 ]. miR-187 was found downregulated in HCC tissues and cell lines: as reported by Han et al[ 29 ], the restoration of miR-187 leads to a significant arrest of HCC growth.…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…miR-187 was found downregulated in HCC tissues and cell lines: as reported by Han et al[ 29 ], the restoration of miR-187 leads to a significant arrest of HCC growth. miR-497 and miR-99a target the 3′-UTR of both IGF-1R and mTOR and were shown to be down-regulated in HCC human tissues and cell lines: the co-transfection with both miRNAs slowed cell proliferation and the tumor growth in HCC cell lines and in xenograft models[ 28 ]. Wang and colleagues demonstrated that miR-592 was significantly downregulated in HCC tissues and cell lines and that its low expression was associated with lymph node metastases[ 30 ].…”
Section: Mirnas In Hcc Molecular Pathwaysmentioning
confidence: 99%
“…Decreased expression of miR-99a-5p was found to predict worse survival in lung adenocarcinoma [27], cervical cancer [28], and breast cancer [29]. MiR-99a-5p was found to play important tumor-suppressive roles, including inhibition of cell proliferation and tumorigenesis by suppressing mTOR signaling pathway and downregulation of insulin-like growth factor 1 receptor [30], and also inhibition of migration and invasion of cancer cells by decreasing MTMR3 protein (Myotubularin-related protein 3) in oral cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that miR-99a may regulate tumor cell proliferation through mTOR, AKT1 and FGFR3 [20][21][22], but detailed studies on the mechanisms of action remain lacking. In this study, MTT assay showed that up-regulating miR-99a inhibited the proliferation of glioma cells, but knocking it down promoted their proliferation.…”
Section: Discussionmentioning
confidence: 99%